Nurses' perceptions of the barriers in effective communicaton with impatient cancer adults in Singapore - Li, H.; Ang, E.; Hegney, Desley (Wiley-Blackwell Publishing Ltd., 2012)
Aim. This study investigated the factors affecting effective communication between Singaporean registered nurses and inpatient oncology adults. Background. In oncology nursing, where conversations entail emotionally loaded topics and patients’ receptivity is greatly affected by their life-threatening disease and its trajectory, effective communication is crucial. Design. This is a qualitative study situated within the interpretivism paradigm. Method. Ten registered nurses from the oncology wards of a major teaching hospital in Singapore were interviewed. Data were transcribed verbatim and thematically analysed. Conclusion. Factors that influenced effective nurse–patient communication were found in the characteristics of the patient, the nurse and the environment. While there are common factors influencing communication in all contexts of practice, this study has suggested that a multicultural community such as Singapore presents special challenges in the oncology inpatient setting. Language barriers are significant, particularly between overseas trained nurses and patients who cannot converse in English. Cultural taboos also increase nurses’ discomfort when discussing sensitive topics. Additionally, the government’s promotion of Singapore as a medical ‘hub’ increases the cultural and ethnic mix of inpatients. A particular concerning finding is Singapore society’s poor perception of and lack of respect for nurses, which is partly contributed by Singapore’s ‘user-pays’ health system and lowly-paid foreign nurses.Relevance to clinical practice. Nurses should be mindful of how patients’ disease trajectory and psychological state affect communication. Nurses should also take patients’ cultural background into consideration when approaching sensitive topics. Language and cultural induction classes should also be made available, especially for overseas trained nurses working in Singapore. Nursing Associations in Singapore need to work on programmes that will increase the prestige of nursing. Further research involving a more representative sample is warranted to understand how Singapore’s ‘user-pays’ health care system affects effective nurse–patient communication.